Contributory factors of accounting information systems effectiveness in Nigerian banking sector - Shagari, Shamsudeen Ladan; Abdullah, Akilah; Mat Saat, Rafeah (2017)
As organizations operate in a highly competitive environment, thus the need for an effective Information System (IS) is inevitable, because IS has the potentials to transform business positively as well as enhancing organizational performance.Many academic researchers have called on the investigation for the role of AIS on the effectiveness of organizations more especially the banking sector.In view of these, this paper attempts to study the influence of system usage and AIS sophistication on AIS effectiveness. Review of existing literature indicated banks in Nigeria are faced with persistent system failure. However, limited attention has been given regarding the issues.Conceptual evidence from the literature reviewed indicated that both system usage and AIS sophistication have a significant relationship with AIS effectiveness.Therefore, this paper develops a conceptual framework for determining AIS effectiveness in Nigerian banking sector with the aim of understanding and providing solutions.